2020
DOI: 10.1371/journal.pcbi.1008202
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic modeling of H2O2 dynamics in the mitochondria of HeLa cells

Abstract: Hydrogen peroxide (H 2 O 2) promotes a range of phenotypes depending on its intracellular concentration and dosing kinetics, including cell death. While this qualitative relationship has been well established, the quantitative and mechanistic aspects of H 2 O 2 signaling are still being elucidated. Mitochondria, a putative source of intracellular H 2 O 2 , have recently been demonstrated to be particularly vulnerable to localized H 2 O 2 perturbations, eliciting a dramatic cell death response in comparison to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 77 publications
0
13
1
Order By: Relevance
“…Moreover, since the concentration of exogenously added H 2 O 2 is likely an over-estimate of intracellular and subcellular accumulation, interpolating local concentrations of H 2 O 2 based on HyPer7 measurements can only provide an upper-bound estimate. Other studies have modeled a 390 to 650-fold difference between extracellular and intracellular H 2 O 2 62,63 and calculated a basal steady-state of 2 to 4 nM in mitochondria 9 . Our experiments never produce a steady-state change approximating greater than 2 μM H 2 O 2 treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, since the concentration of exogenously added H 2 O 2 is likely an over-estimate of intracellular and subcellular accumulation, interpolating local concentrations of H 2 O 2 based on HyPer7 measurements can only provide an upper-bound estimate. Other studies have modeled a 390 to 650-fold difference between extracellular and intracellular H 2 O 2 62,63 and calculated a basal steady-state of 2 to 4 nM in mitochondria 9 . Our experiments never produce a steady-state change approximating greater than 2 μM H 2 O 2 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The exact concentration difference between healthy, metabolically signaling ROS and oxidative damage remains unknown. Once generated, ROS can diffuse between mitochondrial compartments and into the cytosol, but the kinetics of this process is only beginning to be characterized 9,10 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These observations led us to determine which wild-type PRX isoform can form dimers containing some reduced active sites under physiological conditions. For these studies, we used a constant concentration of 100 µM PRX, which is physiologically relevant even if somewhat low for the estimates of PRX3 mitochondrial concentrations (48-125 µM) and slightly higher than the estimated concentration of PRX1 and PRX2 in the cytosol (20-65 µM) [33][34][35]. A recent study using real-time monitoring of the PRX2 oligomerization state confirmed for the first time that PRX2 decamer-dimer oscillations occur and that oxidation favors dimers in cellulo.…”
Section: Discussionmentioning
confidence: 99%